Effects of reactive MgO and metakaolin on compressive strength and chloride migration coefficient of sodium carbonate activated slag mortars - Abolfathi, Mehrnosh; Ulukaya, Serhan; Akturk, Busra (YILDIZ TECHNICAL UNIV, 2023)
This paper presents an investigation of the compressive strength and chloride migration of sodium carbonate (NC) activated slag-based mortars. In the experimental study, NC was preferred to use as an activator since it can be designated as an environment-friendly activator. To improve the performance of sodium carbonate-activated slag-based mortars (NCAS), reactive MgO (M) and metakaolin (MK) were replaced with slag up to 15% by mass and five mortar mixtures were prepared with different M and MK replacement ratios. It was found that replacing the slag with a combination of 10% M and 5% MK achieved the highest compressive strength for both early age and ultimate strength. In addition, the mix which was composed of 85% slag, 10% M and 5% MK, was the most resistant one against chloride migration. Based on the compressive strength and chloride migration test results, it was concluded that the compressive strength and chloride migration performances of NCAS could be enhanced by the combination of M and MK.
Keywords: Alkali-activated Systems; Chloride Migration; Compressive Strength; Slag; Sodium Carbonate; DRYING SHRINKAGE; CEMENT; EVOLUTION; CONCRETE; Engineering